Trade unions’ inflation expectations and the second-round effect in South Africa - Temitope Lydia Leshoro (PSL Quarterly Review, 2018)
Inflation expectations play a critical role in the formation of prices and wages. Hence, the South African Reserve Bank (SARB) reacts to inflation’s direct effects by tightening the monetary policy in order to avoid any second-round effects. The study we conducted attempts to investigate whether the inflation rate are led by inflation expectations or vice versa. We analyse quarterly data using the Toda-Yamamoto causality technique and three different measures of inflation expectations of the trade union representatives. We also investigate the role of the exchange rate in leading or lagging the inflation rate. Overall, the results obtained demonstrate that the inflation and the exchange rates have bidirectional causality, while unidirectional causality exists from the inflation rate to inflation expectations. We therefore conclude that a second-round effect of inflation cannot be induced by changes in the inflation expectations of the trade unions, and provide some policy recommendations.